С.Г.КОЛТУХОВ, А.Е. КИСЛЫЙ, Г.Н.ТОЩЕВ. КУРГАННЫЕ ДРЕВНОСТИ КРЫМА. – Запорожье, 1994. – Выпуск І. С.Г.КОЛТУХОВ, Г.Н.ТОЩЕВ. КУРГАННЫЕ ДРЕВНОСТИ КРЫМА. – Запорожье, 1998. – Выпуск II. (Zaporizhzhia Historical Review, 2020)
-